Streamlined blood handling and leukocyte isolation procedure for immunological applications in hybrid grouper fingerlings, Epinephelus fuscoguttatus × Epinephelus lanceolatus - Abu Aziz, Nurhikmah; Chong, Chou Min; Low, Chen Fei (John Wiley and Sons, 2025)
Isolating leukocytes from small-bodied fish presents significant technical challenges, especially in species such as grouper, which exhibited rapid blood coagulation. Attaining high purity and quality leukocyte recovery in such species is often hindered by clot formation and erythrocyte contamination. Conventional methods using anticoagulants, buffy coat extraction, and density gradient centrifugation are typically labor-intensive and often yielded inconsistent results. In this study, a streamlined and efficient whole blood lysis protocol for isolating leukocytes from grouper fingerling is described. This protocol offers improvements in blood handling, cell recovery, and cryopreservation. The optimized method significantly reduces processing time, preserves cellular integrity, and facilitates downstream applications in fish immunological studies. Overall, this protocol presented a cost-effective and scalable solution for leukocyte isolation in teleost fish, particularly grouper species.